2018
DOI: 10.1111/cpr.12533
|View full text |Cite
|
Sign up to set email alerts
|

IL‐33 guides osteogenesis and increases proliferation and pluripotency marker expression in dental stem cells

Abstract: Objectives Soluble IL‐33 (interleukin (IL)‐1‐like cytokine) acts as endogenous alarm signal (alarmin). Since alarmins, besides activating immune system, act to restore tissue homeostasis, we investigated whether IL‐33 exerts beneficial effects on oral stem cell pull. Materials and Methods Clonogenicity, proliferation, differentiation and senescence of stem cells derived from human periodontal ligament (PDLSCs) and dental pulp (DPSCs) were determined after in vitro expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Activation of NF- κ B also inhibits osteoblast production. The activation of NF- κ B upregulates miRNA-150-3p, inhibiting osteogenesis of mesenchymal stem cells by encouraging β -catenin degradation [ 111 ]. Besides, NF- κ B has a direct role in inhibiting BMP and Wnt signaling and negatively regulates bone mass through sclerostin [ 112 ].…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…Activation of NF- κ B also inhibits osteoblast production. The activation of NF- κ B upregulates miRNA-150-3p, inhibiting osteogenesis of mesenchymal stem cells by encouraging β -catenin degradation [ 111 ]. Besides, NF- κ B has a direct role in inhibiting BMP and Wnt signaling and negatively regulates bone mass through sclerostin [ 112 ].…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…Huh et al reported that IL-6 enhanced osteogenic differentiation of stem cells by activating signal transducer and activator of transcription factor 3 15 . In an in vitro study by Kukolj et al, IL‐33 was found to guide osteogenesis in dental stem cells 17 . On the other hand, another important inflammatory cytokine, IL-1β, was found to suppress osteogenesis and adipogenesis of MSCs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…TNF- α and IL-6 promote the osteogenic differentiation of DPSCs [ 96 , 97 ]. IL-33 treatment impairs osteogenesis of PDLSCs and DPSCs, while pretreated IL-33 can increase osteogenesis of PDLSCs and DPSCs [ 98 ]. The possible reason is that short-term and low-dose stimulation of IL-33 can promote tissue healing, while long-term and high-dose stimulation of IL-33 can aggravate tissue damage.…”
Section: Dental Pulp Stem Cellsmentioning
confidence: 99%